Enhancing student satisfaction via social comparisons - Yumei Mu; Julian Givi; Stephen He (PLoS ONE, 2025)
University tuition and fees impact student engagement and school enrollment. Thus, it is important that students be satisfied with what they are paying. This research incorporates social comparisons in communications to students and examines the impact that these comparisons have on student satisfaction with their cost of attendance and overall university experience. In particular, this work employs an experimental design with two conditions. In the Increase condition, participants learned that a counterpart university planned to increase its tuition and fees, while their own university kept the cost of attendance constant; in the Constant condition, participants learned that both the counterpart university and their own kept tuition and fees constant. The dependent variables were participants’ satisfaction with their own university’s tuition and fees, as well as their overall satisfaction with their university experience. In addition, this research examined relative value as a potential mediating variable influencing these outcomes. The results demonstrate that students become relatively more satisfied when their tuition and fees remain constant, but a counterpart university increases its tuition and fees (the Increase condition) versus keeps these costs constant (the Constant condition). In other words, simply knowing that another university has raised prices (vs. kept them constant) but theirs has not, enhances student satisfaction with tuition and fees, which leads to greater satisfaction with their overall university experience. These findings emerge because students perceive the price they pay for their cost of attendance to be of higher relative value when another university raises prices (vs. keeps them constant). Notably, whereas most research demonstrates how consumer satisfaction can be helped by an organization spending money, this research identifies a cost-free method that universities can use to enhance student satisfaction.